2019
DOI: 10.3389/fmicb.2019.00514
|View full text |Cite
|
Sign up to set email alerts
|

Two Broad Host Range Rhizobial Strains Isolated From Relict Legumes Have Various Complementary Effects on Symbiotic Parameters of Co-inoculated Plants

Abstract: Two bacterial strains Ach-343 and Opo-235 were isolated, respectively from nodules of Miocene-Pliocene relict legumes Astragalus chorinensis Bunge and Oxytropis popoviana Peschkova originated from Buryatia (Baikal Lake region, Russia). For identification of these strains the sequencing of 16S rRNA (rrs) gene was used. Strain Opo-235 belonged to the species Mesorhizobium japonicum, while the strain Ach-343 was identified as M. kowhaii (100 and 99.9% rrs similarity with the type strains MAFF 303099T and ICMP 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
0
18
0
1
Order By: Relevance
“…For example, Sinorhizobium meliloti effectively colonizes Medicago, Melilotus and Trigonella, whereas Rhizobium leguminosarum induces nodules in Pisum vicea, Lens and Lathyrus plants [56]. However, there are also examples of rhizobia with wide host ranges [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sinorhizobium meliloti effectively colonizes Medicago, Melilotus and Trigonella, whereas Rhizobium leguminosarum induces nodules in Pisum vicea, Lens and Lathyrus plants [56]. However, there are also examples of rhizobia with wide host ranges [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…strain CCNWGX022 was isolated from arid and semi-arid regions of China (Wei et al 2007). Mesorhizobium kowhai strain Ach-343 isolated from Astragalus chorinensis Bunge and M. japonicum strain Opo-235 isolated from Oxytropis popoviana Peschkova in Buryatia in the Lake Baikal region of Russia were able to establish symbiosis with G. uralensis (Safronova et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Copyright © 2021 Japanese Society for Plant Biotechnology Phylogenetic analysis of the combined amino acid sequences of nodA, nodB, and nodC from J8 and other Mesorhizobium strains showed that the species most closely related to J8 is Mesorhizobium plurifarium strain WUR2 (Figure 2). These two strains formed a clade distinct from that formed by Mesorhizobium tianshanense strain CCBAU 3306, Mesorhizobium kowhaii Ach-343, and Mesorhizobium japonicum Opo-235, three strains that have been confirmed to establish symbiosis with G. uralensis (Chen et al 2008;Safronova et al 2019).…”
Section: Phylogeny Of the Rhizobium Strain Isolated From G Glabramentioning
confidence: 99%
“…Действительно, хорошо развитая сеть ЭПР была описана для различных видов Astragalus и Oxytropis, как приспособление к произрастанию в арктических условиях [28]. Недавно интенсивное развитие ЭПР было описано для клеток клубеньков реликтового бобового растения O. popoviana, сформированных штаммом M. japonicum Opo-235 [29].…”
Section: обсуждение результатовunclassified